ALOE VERA BECOMES A FAMILY BUSINESS OPPORTUNITY: LIDAH BUAYA MENJADI PELUANG BISNIS KELUARGA - Erna Haryanti; Dwi Haryanta; Endang Retno Wedowati; Dwie Retna Suryaningsih; Cindy Sulistyawati (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Aloe vera is a plant that has long been known to the public, but it is still a wild plant that is not cultivated properly. The development of science and technology changes the image of aloe vera into a plant that has many benefits, and becomes a business opportunity. This motivated the community service team from the Faculty of Agriculture, Wijaya Kusuma University, Surabaya to provide assistance to economically non-productive mothers to take advantage of this business opportunity. The team's optimism is supported by the local potential of the aloe vera plant, as well as encouragement from village government agencies and the community. It was carried out in Wonoanti Village, Gandusari District, Trenggalek Regency by using the PRRA (Participatory Rapid Rural Appraissal) and RRA (Rapid and Rural Appraissal) methods. Through this activity, the target is equipped with practical business management and marketing knowledge, entrepreneurial motivation, as well as practical activities and assistance for cultivation, processing of aloe vera products, so that the target is to master cultivation techniques and appropriate technology (TTG) processing aloe vera products into processed products that are developed. as a profitable and sustainable entrepreneurial activity